2020
DOI: 10.3390/ijms21030710
|View full text |Cite
|
Sign up to set email alerts
|

The Flagellar Gene Regulates Biofilm Formation and Mussel Larval Settlement and Metamorphosis

Abstract: Biofilms are critical components of most marine systems and provide biochemical cues that can significantly impact overall community composition. Although progress has been made in the bacteria–animal interaction, the molecular basis of modulation of settlement and metamorphosis in most marine animals by bacteria is poorly understood. Here, Pseudoalteromonas marina showing inducing activity on mussel settlement and metamorphosis was chosen as a model to clarify the mechanism that regulates the bacteria–mussel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…We found that flagellar assembly protein fliH (RF53_RS02940) participating in cell motility was significantly downregulated in FUR-exposed P. marina biofilms relative to the CTR biofilms. Our recent study also demonstrates that a flagellin synthetic protein gene fliP deletion of P. marina contributes to the loss of the flagella structure and motility (Liang et al, 2020). The flagellum is critical for the mobility of bacteria, which is crucial for the initial surface attachment, subsequent biofilm formation and virulence (O'Toole and Kolter, 1998;Watnick et al, 2001;Lemon et al, 2007;Liang et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We found that flagellar assembly protein fliH (RF53_RS02940) participating in cell motility was significantly downregulated in FUR-exposed P. marina biofilms relative to the CTR biofilms. Our recent study also demonstrates that a flagellin synthetic protein gene fliP deletion of P. marina contributes to the loss of the flagella structure and motility (Liang et al, 2020). The flagellum is critical for the mobility of bacteria, which is crucial for the initial surface attachment, subsequent biofilm formation and virulence (O'Toole and Kolter, 1998;Watnick et al, 2001;Lemon et al, 2007;Liang et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…The 10 −4 M FUR-treated biofilms were selected for biofilm staining due to the lowest plantigrade settlement rate for comparing the individual components in the biofilm matrix. The visualization of proteins, lipids, α-polysaccharides, and β-polysaccharides in the P. marina ECSMB14103 biofilms was carried out by following a previously described method (González-Machado et al, 2018;Liang et al, 2020). Four fluorescent dyes, including fluorescein isothiocyanate isomer I (FITC), DiIC 18 (5) oil, 1,1 -dioctadecyl-3,3,3 ,3tetramethylindodicarbocyanine perchlorate (DiD oil; Invitrogen D307), concanavalin A, tetramethylrhodamine conjugate (ConA-TmR; Invitrogen C860), and calcofluor white M2R (CFW; Sigma 18909) were used for staining the proteins, lipids, α-polysaccharides, and β-polysaccharides, respectively.…”
Section: Biofilm Staining Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Treated BFs (100H, 10A and FF) without alive bacteria showed low inducing activity, indicating that the living deep-sea bacteria is necessary to produce chemical signals to promote the settlement process in this species. Previous studies have also demonstrated that the settlement process of M. coruscus [10][11][12][13] larvae also required BFs of living offshore bacteria, as well as M. galloprovincialis 8 and H. elegans 20,24 larvae.…”
Section: Discussionmentioning
confidence: 90%
“…Confocal laser scanning microscopy (CLSM) and image analysis. Extracellular products were stained according to the method of Liang et al 12 . Virgibacillus sp.…”
mentioning
confidence: 99%